2007
DOI: 10.1523/jneurosci.0012-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Glutamatergic Afferents of the Ventral Tegmental Area in the Rat

Abstract: Glutamatergic inputs to the ventral tegmental area (VTA), thought crucial to the capacity of the VTA to detect and signal stimulus salience, have been reported to arise in but a few structures. However, the afferent system of the VTA comprises very abundant neurons within a large formation extending from the prefrontal cortex to the caudal brainstem. Neurons in nearly all parts of this continuum may be glutamatergic and equivalently important to VTA function. Thus, we sought to identify the full range of gluta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
428
2
5

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 423 publications
(461 citation statements)
references
References 47 publications
26
428
2
5
Order By: Relevance
“…Despite the apparent VGLUT3-ir PBs, VGLUT3-mRNA was not expressed in LS neurons in all these studies; a finding that was recently confirmed by Geisler et al (2007). In contrast, VGLUT3-mRNA was found in deeper brain areas like hypothalamus, substantia nigra and dorsal raphe (Fremeau et al, 2002;Gras et al, 2002;Herzog et al, 2004;Schäfer et al, 2002).…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…Despite the apparent VGLUT3-ir PBs, VGLUT3-mRNA was not expressed in LS neurons in all these studies; a finding that was recently confirmed by Geisler et al (2007). In contrast, VGLUT3-mRNA was found in deeper brain areas like hypothalamus, substantia nigra and dorsal raphe (Fremeau et al, 2002;Gras et al, 2002;Herzog et al, 2004;Schäfer et al, 2002).…”
Section: Introductionmentioning
confidence: 72%
“…These results indicate that an origin of VGLUT3-ir afferents from a deeper brainstem modulatory system is probable. The median and dorsal raphe nuclei are potent candidates for these VGLUT3-ir projections as they have been shown to be the origin of VGLUT3-positive projections to a variety of brain regions (Geisler et al, 2007;Hioki et al, 2004;Somogyi et al, 2004). Tract tracing studies will elucidate whether the VGLUT3-ir fibers originate in pure glutamatergic neurons or in neurons that co-produce another transmitter, but release the glutamate at different sites.…”
Section: Coincidence Of Vglut3-ir With Markers That Define Minor Neurmentioning
confidence: 99%
“…The VTA primarily receives excitatory neuronal input from the PFC while receiving inhibitory input from the amygdala. 132 Acute administration of morphine directly into the VTA induces release of DA in the NAc as measured by microdialysis in rats. 133 This coincides with increased firing of dopaminergic neurons in the VTA with acute IV morphine.…”
Section: Molecular Changes In the Ventral Tegmental Areamentioning
confidence: 99%
“…A possible answer could be that the mesolimbic pathway is also involved in executive tasks indirectly, by regulating activity in the mesocortical pathway (e.g. via ACC-to-VTA projections) (Devinsky, Morrell, & Vogt, 1995;Geisler, Derst, Veh, & Zahm, 2007) (Yu & Dayan, 2005). Hence, one can hypothesize that ACC impairments could be at least partially responsible for the executive dysfunctions in ADHD via LC dysregulation.…”
Section: Relations With the Dual-pathway Modelmentioning
confidence: 99%